2016
DOI: 10.3390/ijms17091458
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Modify the Response of Prostate Cancer Cells to Androgen and Anti-Androgens in Three-Dimensional Spheroid Culture

Abstract: Androgen receptor (AR) targeting remains the gold standard treatment for advanced prostate cancer (PCa); however, treatment resistance remains a major clinical problem. To study the therapeutic effects of clinically used anti-androgens we characterized herein a tissue-mimetic three-dimensional (3D) in vitro model whereby PCa cells were cultured alone or with PCa-associated fibroblasts (CAFs). Notably, the ratio of PCa cells to CAFs significantly increased in time in favor of the tumor cells within the spheroid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…In a previous study we showed that PCa cells become less responsive to enzalutamide when they are cocultured as tumor spheroids in a 3-dimensional environment together with cancer-associated fibroblasts (CAFs) [11]. In this study, we performed gene expression profiling of these co-culture spheroids and revealed that CAFs induce a significant upregulation of cholesterol metabolism and steroid biosynthesis in PCa cells.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study we showed that PCa cells become less responsive to enzalutamide when they are cocultured as tumor spheroids in a 3-dimensional environment together with cancer-associated fibroblasts (CAFs) [11]. In this study, we performed gene expression profiling of these co-culture spheroids and revealed that CAFs induce a significant upregulation of cholesterol metabolism and steroid biosynthesis in PCa cells.…”
Section: Introductionmentioning
confidence: 90%
“…The androgenablated subline LNCaPabl was previously established by long-term culture in androgen-ablated medium [12] and maintained in RPMI 1640 (Lonza) with 10% charcoalstripped (CS) FCS and 1% penicillin and streptomycin. Immortalized CAFs [13] stably expressing green fluorescent protein (GFP) have been previously established [11] and were grown in DMEM with 10% FCS and 1% penicillin and streptomycin and 1x GlutaMAX™ (Gibco). The enzalutamide resistant (EnzaR) cell lines DuCaP EnzaR and LNCaPabl EnzaR have been previously established by long-term treatment with 8 μM enzalutamide [14].…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…fibroblasts (CCD-18Co;Jeong, Lee, Shin, Chung, & Kuh, 2016); prostate cancer cells (LNCaP and DuCaP) and CAF (Eder et al, 2016) and SU6668 [Joyce, 2005]) have also been studied.…”
Section: Heterogenic Cellular Constitutionmentioning
confidence: 99%
“…fibroblasts (CCD-18Co;Jeong, Lee, Shin, Chung, & Kuh, 2016); prostate cancer cells (LNCaP and DuCaP) and CAF (Eder et al, 2016); breast cancer cells (MDA-MB-231) and microvascular endothelial cells (HMEC-1) (Kassim, Al Tawil, Buquet, Le Cerf, & PierreVannier, 2017); pancreatic cancer cells (PANC-1) and pancreatic stellate cells (myofibroblast-like cells; J.-H. .…”
Section: Heterogenic Cellular Constitutionmentioning
confidence: 99%
“…1 While epithelial in origin, the tumor microenvironment plays a critical role in prostate adenocarcinoma pathogenesis, for example, stromal signaling is required for tumor initiation, tumor cell proliferation, angiogenesis, metastasis and diminishes therapy response. [2][3][4] These protumorigenic actions of the tumor microenvironment are largely mediated via the secretion of…”
mentioning
confidence: 99%